What is sociolinguistics? - Van Herk, Gerard (Wiley-Blackwell, 2012)
"What is Sociolinguistics? is a tour through the major issues that define the field, such as region, status, gender, time, language attitudes, interaction, and style, while also exploring the sociolinguistics of multilingualism, culture and ethnicity, language contact, and education, all introduced with excitement, humor, and deep knowledge. Explores the sociolinguistics of multilingualism, culture and ethnicity, language contact, and education Provides useful and clear learning features including numerous innovative exercises and project ideas, spotlighted research readings, glossary terms, chapter summaries, and text boxes Features a companion website offering PowerPoint slides for instructors and sample answers to questions, as well as links for further study.--Resumé vydavatele
Terminologický slovník
Keywords: sociolingvistika; sociolinguistics; příručky; handbooks, manuals, etc